Utilization of Digital Development in the Creation of Village Development Websites and Profile Compilation - Khairina, Dyna Marisa; Maharani, Septya; Amriani, Nilda; Laden, Delfan Rynaldo; Syahputra, Oktavian Yoga; Arsuwendi, Arsuwendi; Sunarto, Suhaera; Aisyah, Nur; Arham, Zulvika Anisa; Syahril, Syahril (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study explores the use of information technology in Indonesian Neighborhood Associations (RT), focusing on RT 32 in Sempaja Timur Village. It investigates how a village website enhances community engagement and promotes local SMEs, contributing to smoother governance processes. Method: Employing qualitative methods, including interviews and document analysis, the study examines the development of the village website. Thematic coding identifies key themes related to community participation and economic empowerment. Practical Applications: The findings inform community development practitioners, policymakers, and technologists about the benefits of digital platforms for participatory governance and economic growth in similar contexts. Conclusion: Leveraging information technology can empower communities, as seen in RT 32's case. Digital platforms facilitate communication, economic activities, and community cohesion, offering insights for grassroots development efforts.